2016
DOI: 10.4103/0975-962x.174594
|View full text |Cite
|
Sign up to set email alerts
|

Unusual giant sialolith of Wharton's duct

Abstract: Salivary gland calculi account for the most common disease of the salivary glands. Most of the salivary calculi are small in size. Some calculi that reach several centimeters are reported as megaliths or giant calculi in the literature. They may occur in any of the salivary gland ducts but are most common in Wharton's duct and in the submandibular gland. This report presents clinical and radiographical sign of an unusually large sialolith. A patient came with pain in the floor of mouth. There was a swelling on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 8 publications
0
13
0
5
Order By: Relevance
“…[22] There were several reports on the removal of giant sialoliths intra-orally, but all of them had calculi described within the distal portion of the Wharton's duct. Among the case reports were from Soares, et al [3,20,29,[30][31][32][33] However, there was one case reported of an intraoral removal of giant sialolith (25 mm) located at the proximal part of Wharton's duct but it was not mentioned whether it was extending into the intra-glandular ductal at the hilum and causing obstruction as in our case. [23] A study by Park, et al (2012) to identify a surgical landmark for a suitable approach to remove proximal Wharton's duct and hilum sialoliths, found that all of 74 patients had successfully underwent intraoral removal of the sialoliths with a mean size of 8 mm, which was below the size of giant sialolith.…”
Section: Discussionmentioning
confidence: 87%
“…[22] There were several reports on the removal of giant sialoliths intra-orally, but all of them had calculi described within the distal portion of the Wharton's duct. Among the case reports were from Soares, et al [3,20,29,[30][31][32][33] However, there was one case reported of an intraoral removal of giant sialolith (25 mm) located at the proximal part of Wharton's duct but it was not mentioned whether it was extending into the intra-glandular ductal at the hilum and causing obstruction as in our case. [23] A study by Park, et al (2012) to identify a surgical landmark for a suitable approach to remove proximal Wharton's duct and hilum sialoliths, found that all of 74 patients had successfully underwent intraoral removal of the sialoliths with a mean size of 8 mm, which was below the size of giant sialolith.…”
Section: Discussionmentioning
confidence: 87%
“…The aetiology of sialolithiasis is still unknown, but some authors believe that persistent changes in saliva flow along with an increased amount of mucus facilitates the precipitation of amorphous phosphate tricalcium [2, 3, 5, 8], which becomes crystallised and transforms into hydroxyapatite. From this matrix, there is an apposition of several substances which also become calcified and form the sialolith [2, 3, 5, 6, 8].…”
Section: Discussionmentioning
confidence: 99%
“…In general, they are asymptomatic, presenting a slight increase in glandular volume during salivary stimulation, which causes a mild sensation of discomfort [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations